2021
DOI: 10.3390/nu13072420
|View full text |Cite
|
Sign up to set email alerts
|

Eating Speed, Physical Activity, and Cardiorespiratory Fitness Are Independent Predictors of Metabolic Syndrome in Korean University Students

Abstract: Background: Little is known regarding the role of eating quickly, physical inactivity, and poor cardiorespiratory fitness (CRF) in assessing the onset of metabolic syndrome (Mets) in Korean young adults. Objectives: This study examined the association between the three risk factors and Mets in 1891 Korean university students (30% female) aged 18–29 years. Methods: Eating speed (slow vs. fast) and physical activity (active vs. inactive) were assessed with a standardized questionnaire. Maximal oxygen uptake as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The sample of participants was only female in five studies [ 34 , 38 , 40 , 41 , 43 ], while only one study had male participants only [ 47 ]. There were eight studies where the sample of participants was from the Faculty of Sport and Physical Education students [ 30 , 31 , 33 , 35 , 37 , 40 , 41 , 43 ], only one study had Criminal Police Academy students [ 36 ], while the rest of the studies had participants from different universities and faculties [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample of participants was only female in five studies [ 34 , 38 , 40 , 41 , 43 ], while only one study had male participants only [ 47 ]. There were eight studies where the sample of participants was from the Faculty of Sport and Physical Education students [ 30 , 31 , 33 , 35 , 37 , 40 , 41 , 43 ], only one study had Criminal Police Academy students [ 36 ], while the rest of the studies had participants from different universities and faculties [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies had students from Poland National University [ 45 , 46 ], one had Tsingua University students from China [ 44 ], and all three mentioned were using their own standardized battery test. Aqua-Pilates program [ 40 ], Bamboo dance program [ 39 ], hiking activities [ 35 ], and fitness yoga [ 38 ] were also evaluated and there were also two studies that conducted VO2max evaluation on the treadmill [ 49 ] and cycle ergometer [ 50 ]. The rest of the studies were using standard and already known physical fitness tests.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The epidemiological data has demonstrated that BMI, physical activity and energy intake is associated with both dietary vitamin E and MetS (59)(60)(61)(62)(63). Indeed, our finding is lost in studies without adjustment of these factors (Table 2).…”
Section: Discussionmentioning
confidence: 70%